Determinants of Indonesian telecommunications industry’s firm value with dividend policy as the moderating variable - Fakhirah Husain; Masdar Mas'ud; Syamsu Alam (Journal of Enterprise and Development (JED), 2023)
Purpose — This study attempts to investigate the effect of profitability and capital structure on firm value with dividend policy as a moderating variable.Method — The populations were all telecommunications companies listed on the Indonesia Stock Exchange (IDX) for 2012 to 2021, totaling 19 companies. Using the purposive sampling technique, three companies were used as a sample with a time series for 10 years. The collected secondary data was then analyzed by multiple regression analysis techniques and Moderated Regression Analysis (MRA) supported by SPSS (Statistical Product and Service Solutions) application tools to confirm the research hypothesis. Result — The results indicated that profitability has a positive and significant effect on firm value, while capital structure has no significant effect on firm value. Dividend policy was able to moderate the effect of profitability on firm value, but dividend policy was not able to moderate the capital structure on firm value. Contribution — This research contributes mainly to the firm value literature by strengthening grand theories used in Indonesian telecommunication sectors.